Adipocytokine plasma concentrations reflect influence of inflammation but not body mass index (BMI) on clinical outcomes of COVID‐19 patients: A prospective observational study from the Netherlands. Issue 2 (25th November 2022) - de Nooijer, Aline H.; Kooistra, Emma J.; Grondman, Inge; Janssen, Nico A. F.; Joosten, Leo A. B.; van de Veerdonk, Frank L.; Kox, Matthijs; Pickkers, Peter; Netea, Mihai G.; ,
Summary: Obesity is recognized as a risk factor for adverse outcome in COVID‐19, but the molecular mechanisms underlying this relationship remain unknown. Adipose tissue functions as an endocrine organ by secreting multiple pro‐inflammatory and anti‐inflammatory factors, known as adipocytokines, which could be involved in COVID‐19 severity. We explored the role of adipocytokines in COVID‐19 and its association with BMI, clinical outcome, and inflammation. This is an observational study in 195 hospitalized COVID‐19 patients. Serial plasma concentrations of the adipocytokines leptin, adiponectin, resistin, and various inflammatory cytokines were assessed. Adipocytokines were compared between patients with normal weight (BMI: 18.5–24.9 kg/m 2 ), overweight (BMI: 25.0–29.9 kg/m 2 ), and obesity (BMI ≥ 30 kg/m 2 ), between patients admitted to the ICU and to non‐ICU clinical wards, and between survivors and non‐survivors. Patients with overweight and obesity displayed higher leptin concentrations and lower adiponectin concentrations throughout hospital admission ( p < .001), whereas resistin concentrations were not different from patients with normal weight ( p = .12). Resistin concentrations correlated with inflammatory markers and were persistently higher in ICU patients and non‐survivors compared to non‐ICU patients and survivors, respectively (both p < .001), whereas no such relationships were found for the other adipocytokines. In conclusion, leptin and adiponectin are associated with BMI, but not with clinical outcomes and inflammation in COVID‐19 patients. In contrast, resistin is not associated with BMI, but high concentrations are associated with worse clinical outcomes and more pronounced inflammation. Therefore, it is unlikely that BMI‐related adipocytokines or differences in the inflammatory response underlie obesity as a risk factor for severe COVID‐19.